Mistakes in Mathematics Problems Solving Based on Newman's Error Analysis on Set Materials - Sutidte Noutsara; Tumkom Neunjhem; Watchaeeya Chemrutsame (Newinera Publisher, 2021)
The purpose of this research is to illustrate students' errors using Newman's methods for working on problems in mathematical set materials as a basis for description. For the purpose of gathering data, researchers make observations both before the start of a study and throughout the course of the study, that is, when students are working on the exams that are provided. Unstructured observation is the kind of observation that will be utilized by researchers in their investigations. The exam is also used to evaluate students' errors in completing math narrative problems using provided material, which is based on Newman's Error Analysis. During the interviews, students are interviewed one at a time in order to make it simpler for researchers to explain the errors they made while attempting to solve the provided issue. The result of the study shows that High Ability Category experience reading and comprehension errors. They also experience a transformation error in the problem-solving stage of the problem. The problem of process skill is to determine the slice of the set. The answer obtained is not correct and does not match the answer on the question, so the subject makes a mistake at the skill stage of the process